Trotsky subversivo: ausencias y presencias en el imaginario cubano (Revista de Crítica Literaria Latinoamericana, 2015)
Leon Trotsky was banned in Cuba until the end of the Soviet Union. Trotsky, however, was linked to Cuban history for several reasons: Eustaquia María Caridad del Río Hernández, mother of Ramón Mercader, Trotsky’s murderer, was of Cuban origin; Mercader also lived his last years in Cuba, from 1974 to 1978. Moreover, Cuba could have been a destination for the exiled Trotsky in 1916. From these historical coincidences, the fictional stories narrated by Frank Delgado in his song of 1997, “Trotsky’s cha-cha-cha” (disc La Habana está de bala), and Leonardo Padura’s novel The Man Who Loved Dogs (2009) are discussed in tandem. My article examines how Padura and Delgado propose a subversive reading of Trotsky from the deconstruction of the historical figures and human presentation of both characters, Mercader and Trotsky.
Keywords: León Trotsky; Ramón Mercader; Soviet Union; Post-Soviet Cuba; Deconstruction; Subversion; Historical novel